(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1993)
This paper considers the thermodynamies of the following tribologic system: two cy;linders (shafts), one of which is evenly rotating, are rubbing along to their contact surface. A spherical model of rough surface is assumed, and a formula for the number of asperies has been found. It is shown thath the temperature of asperities at the friction reaches its maximum on the basis of the assuption that the cylinders are thermal-insulated at a shallow depth.